Low-frequency noise and DC I-V characterization of gamma-ray irradiation-induced degradation and trap behaviors in a-IGZO TFTs - Lee, Hongseung; Yoo, Jaewook; Song, Hyeonjun; Lee, Binhyeong; Yoon, Soon Joo; Lim, Seongbin; Jeong, Jo Hak; Kim, Soyeon; Park, Minah; Park, Seohyeon; Jung, Sojin; Pandit, Bhishma; et al. (Applied Physics Letters, 2025)
This work reports the impact of gamma-ray (γ-ray) irradiation-induced degradation based on the trap behaviors in amorphous indium-gallium-zinc-oxide (a-IGZO) thin-film transistors. By employing multiple measurement configurations via low-frequency noise and direct current I-V characterization, we quantitatively investigated the energetic distribution of subgap density-of-states in the a-IGZO channel and the spatial distribution of oxide traps (Not) in the gate insulator, respectively. Also, the qualitative analysis was performed to determine the oxygen-related defects after γ-ray irradiation using x-ray photoelectron spectroscopy. Furthermore, the validity of our results was additionally confirmed by measuring the breakdown voltage and applying positive-bias stress to the fabricated devices exposed to radiation for accelerated tests.
Keywords: Amorphous-indium gallium zinc oxides; Degradation behavior; Gamma rays irradiation; Gamma-rays; Irradiation-induced degradation; Low-Frequency Noise; Oxide TFTs; Oxide thinfilm transistors (TFTs); Trap behavior; Zinc oxide thin films